Splenic trauma in a patient with portal hypertension and splenomegaly: A case report - Topçu, Ahmet; Başak, Fatih (Journal of Surgery and Medicine, 2017)
The spleen is the most commonly injured organ in cases of blunt abdominal trauma. Currently, 50-80% of adults with blunt splenic injuries are treated nonoperatively. In this report, we present a blunt abdominal trauma patient having a history of portal hypertension and splenomegaly. In grade 3 and even grade 4 splenic injuries non-operative treatment is recommended in current literature. Management of splenic trauma with a patient with history of splenomegaly and portal hypertension is insufficiently discussed in literature. In presented case, hypersplenism and portal hypertension were burden on hemostasis. Even with massive resuscitation, thrombocyte level decreased to 40.000/mm³ after five hours. But, insistence on non-operative treatment in this situation could be fatal.